1990
DOI: 10.1111/j.1469-8986.1990.tb00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Rudimentary Physiological Effects of Mere Observation

Abstract: Complex social factors can influence physiological activity, behavior, and health, but little is known about how essential components of these factors (e.g., human association, observation) affect human physiology. To begin to address this issue, an experiment was conducted to contrast predictions from social facilitation, distraction/conflict, and physiological reactivity formulations regarding the physiological effects of mere observation. Skin conductance and heart rate were measured surreptitiously from 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 32 publications
5
50
0
2
Order By: Relevance
“…According to our findings, explicit social evaluation is not necessary to boost potential motivation and test anxiety plays no significant role in the determination of cardiovascular reactivity under social evaluation-as the zero-effect of this variable as a covariate indicated. Moreover, observers who are physically present during task performance seem to have different effects than people who are merely present without a performance context (see Cacioppo et al, 1990;Vrana and Rollock, 1998).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to our findings, explicit social evaluation is not necessary to boost potential motivation and test anxiety plays no significant role in the determination of cardiovascular reactivity under social evaluation-as the zero-effect of this variable as a covariate indicated. Moreover, observers who are physically present during task performance seem to have different effects than people who are merely present without a performance context (see Cacioppo et al, 1990;Vrana and Rollock, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Cacioppo et al (1990) found that being observed resulted in increased skin conductance in response to a presented orienting tone. Vrana and Rollock (1998) reported (among other autonomic indices) heart rate increases caused by a minimal social encounter with an experimenter entering the laboratory and taking participants' pulse.…”
Section: Introductionmentioning
confidence: 96%
“…have found that startle responses are smaller when one is being observed and have hypothesized this finding as indicating withdrawal of attention from the environment. However, there are alternative explanations for startle diminution while being observed~Lang, Bradley, & Cuthbert, 1997!, and other studies have suggested that being observed leads to greater responsivity to the environment~Cacioppo, Rourke, Marshall-Goodell, Tassinary, & Baron, 1990!. Hypothesizing about the probable impact of self-focus-induced negative mood is more straightforward. The magnitude of the startle response is larger while viewing unpleasant pictures than while viewing pleasant pictures, regardless of the sensory modality in which the startle occurs~Bradley, Cuthbert, & Lang, 1990;Vrana, Spence, & Lang, 1988!.…”
Section: The Startle Reflex As a Probe Into Attention And Emotionmentioning
confidence: 98%
“…We predicted that this would lead to a relative implicit preference for the concept paired with positive versus negative. As concepts characterized by weak a priori attitudes are more susceptible to conditioning (e.g., Cacioppo, Marshall Goodell, Tassinary, & Petty, 1992), we used letters of the alphabet (I vs. O) and names of unknown social groups (Luupites vs. Niffites) as attitude objects (Gregg, Seibt, & Banaji, 2006;Nuttin, 1985Nuttin, , 1987. Each participant performed one IAT task.…”
Section: Prestudies 1-3mentioning
confidence: 99%